An instrumented timed up and go in facioscapulohumeral muscular dystrophy. Issue 3 (6th October 2017) - Huisinga, Jessie; Bruetsch, Adam; Mccalley, Ayla; Currence, Melissa; Herbelin, Laura; Jawdat, Omar; Pasnoor, Mamatha; Dimachkie, Mazen; Barohn, Richard; Statland, Jeffrey
ABSTRACT: Introduction : Instrumenting timed functional motor tasks may reveal a continuum of motor disability that predicts future motor dysfunction. Methods : We performed a prospective study of the instrumented timed up and go (iTUG) test in genetically confirmed facioscapulohumeral muscular dystrophy (FSHD) participants using a commercially available system of wireless motion sensors. Patients returned within 2 weeks to determine test–retest reliability. Gait parameters in FSHD participants were compared with a normative database, FSHD clinical severity score, manual muscle testing, and patient‐reported functional disability. Results : Gait parameters in FSHD participants were significantly ( P < 0.05) altered compared with normative values, and reliability was excellent (intraclass correlation coefficient 0.84–0.99). Stride velocity and trunk sagittal range of motion had moderate to strong correlations to other FSHD disease measures. Discussion : The iTUG was reliable, abnormal in FSHD, and could distinguish between participants with differing disease severities. Instrumenting timed functional tasks may prove to be useful in FSHD clinical trials. Muscle Nerve 57 : 503–506, 2018